Novel insights into the clinical and molecular spectrum of congenital disorders of autophagy. Issue 1 (8th April 2019) - Teinert, Julian; Behne, Robert; Wimmer, Miriam; Ebrahimi‐Fakhari, Darius
Abstract: Autophagy is a fundamental and conserved catabolic pathway that mediates the degradation of macromolecules and organelles in lysosomes. Autophagy is particularly important to postmitotic and metabolically active cells such as neurons. The complex architecture of neurons and their long axons pose additional challenges for efficient recycling of cargo. Not surprisingly autophagy is required for normal central nervous system development and function. Several single‐gene disorders of the autophagy pathway have been discovered in recent years giving rise to a novel group of inborn errors of metabolism referred to as congenital disorders of autophagy . While these disorders are heterogeneous, they share several clinical and molecular characteristics including a prominent and progressive involvement of the central nervous system leading to brain malformations, developmental delay, intellectual disability, epilepsy, movement disorders, and cognitive decline. On brain magnetic resonance imaging a predominant involvement of the corpus callosum, the corticospinal tracts and the cerebellum are noted. A storage disease phenotype is present in some diseases, underscoring both clinical and molecular overlaps to lysosomal storage diseases. This review provides an update on the clinical, imaging, and genetic spectrum of congenital disorders of autophagy and highlights the importance of this pathway for neurometabolism and childhood‐onset neurological diseases.